Demand for gasoline is more price-inelastic than it is commonly thought - Tomáš Havránek; Zuzana Iršová; Karel Janda (Charles University in Prague, Institute of Economic Studies (IES), 2011)
One of the most frequently examined statistical relationships in energy economics has been the price elasticity of gasoline demand. We conduct a quantitative survey of the estimates of elasticity reported for various countries around the world. Our meta-analysis indicates that the literature suffers from publication selection bias: insignificant and positive estimates of the price elasticity are rarely reported, although implausibly large negative estimates are reported regularly. In consequence, the average published estimates of both short- and long-run elasticities are exaggerated twofold. Using mixed-effects multilevel meta-regression, we show that after correction for publication bias the average long-run elasticity reaches -0.31 and the average short-run elasticity only -0.09
Keywords: C83; Q41; Q48; 330; Gasoline demand; Price elasticity; Meta-analysis; Publication selection bias